A Comparative Analysis of Kartosuwiryo's Thoughts on Faith, Hijrah, and Jihad through the Lens of Tafsir Al-Azhar - Rizky, Vikri Muhamad; Mualim, Mohamad; Ghianovan, Jaka (TAFSE: Journal of Qur'anic Studies, 2024)
This study aims to examine and compare the ideological visions of Sekarmaji Marijan Kartosuwiryo with Hamka's interpretations in Tafsir Al-Azhar, particularly regarding the Islamic concepts of faith, migration (hijrah), and jihad, and their implications for the formation of an Islamic state in post-independence Indonesia. Employing a comparative analysis methodology and bibliographic research approach, this study collected and analyzed data from a variety of primary and secondary sources, including books, journal articles, and historical documentation. The analysis reveals fundamental differences between Kartosuwiryo, who advocates for the establishment of an Islamic state based on strict Sharia principles with a radical approach, and Hamka, who emphasizes the necessity of spiritual and moral transformation through hijrah and jihad. While Kartosuwiryo views hijrah and jihad as political tools for social and political restructuring, Hamka interprets these concepts as a spiritual journey supporting internal change and personal growth.